Health education with hypertensive illiterates: experience report - Lívia Augusta César da Silva Pereira, Claudete Ferreira de Souza Monteiro, Maria da Conceição de Souza Melo, Isabelly Cristina Honorato de Queiroz (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.8esp77-80